PS-b-PEG Block Copolymer for the Compatibility of the Electro Spun Fiber of PS/PEG Blend - You, Minghui; Sun, Qixiang; Zhang, Shuo; Liu, Jingsheng (Current Nanoscience, 2018)
Background: The electrospining of Poly (styrene)/poly(ethylene glycol) blend and prepared electrospun Poly (styrene)/poly(ethylene glycol) are the composite fibers. The Core-shell structured PS-PEG fibers were founded by polarized optical microscope after electrospinning, meanwhile, the mechanism of structure was also discussed. Methods: The Electro-spinning is a facile method to fabricate polymer fibers. The single-step process to fabricate poly (styrene)(PS)/poly(ethylene glycol)(PEG) polymer nano-fiber meshes had been investigated, respectively. The morphology and crystallization behavior of the blend were observed by polarized optical microscopy. Results: The clear phase separation of PEG encapsulating on the PS fiber surface, and the nano-fiber composed of a core-shell structure, furthermore, the core of PS with the shell of PEG were observed, respectively. To increase the compatibility of the PS/PEG blend, Poly (styrene)(PS)-b-poly(ethylene glycol)(PEG), synthesized via atom transfer radical polymerization (ATRP) was introduced. The addition of the PS-b-PEG block copolymer has no negative effect on the electro-spinning process. Conclusion: When the Block copolymer of PS-b-PEG as a compatibilizer was added into the PS/PEG blend, the homogeneous electrospun fibers without phase separation was obtained. The effect of PS-b-PEG block copolymer on electrospinning of PS/PEG blend was analyzed by evaluating the morphology and crystallization behavior of the electrospun fibers. Under polarized optical microscopy analyses suggest that, it can be found that the phase separation between PS and PEG disappears due to the introduction of the compatibilizer. Meanwhile, the core-shell structure of PEG/PS composite fiber was destroyed and PEG evenly dispersed in PS/PEG blend.
Keywords: nanomaterials